Genome-wide characterization of Salmonella enterica serovars circulating in the Brazilian animal food production chain - Monte, Daniel Farias Marinho do (2019)
Salmonella enterica remains one of the most important global foodborne pathogens identified in foods, food-producing animals, environmental sources and humans. Recently, an increase in antibiotic-resistant S. enterica has caused global concern as treatment options become limited. As a result, the World Health Organization has deemed antibiotic-resistant S. enterica a high-priority bacterium. Thus, there is a need to monitor the rise and occurrence of S. enterica serotypes, and to strengthen surveillance of all serotypes that are a pathogenic threat and may carry relevant antimicrobial resistance and virulence genes. Additionally, the high diversity of S. enterica genome makes the efforts more difficult for developing mitigation strategies to aid in the reduction of this pathogen. Considering these aspects, the aim of this PhD study was to investigate the distribution of S. enterica serovars isolated from different sources over a 16-year period. Furthermore, to examine the current resistome and virulome of these strains, since these aspects constantly change and adapt to new surroundings. Finally, investigate the relatedness between these strains through phylogenomics, and the implication of persistent strains and their impacts on one health. In Monte I, we addressed a review of the current insights regarding S. enterica in food and foodstuffs highlighting the most important aspects of high priority antibiotic-resistant S. enterica. In Monte II, we investigated two hundred and sixty-four S. enterica isolates recovered over a 16-year period from the poultry and swine production chains, in Brazil, by whole-genome sequencing (WGS). Most international lineages belonging to 29 serovars, including, S. enterica serovars S. Schwarzengrund sequence type (ST) 96, S. Typhimurium ST19, S. Minnesota ST548, S. Infantis ST32, S. Heidelberg ST15, S. Newport ST45, S. Brandenburg ST65 and S. Kentucky ST198 displayed multi-drug resistant (MDR) and virulent genetic backgrounds. In this regard, resistome analysis revealed presence of qnrE1, qnrB19, qnrS1, blaCTX-M-8, blaCTX-M-2 and blaCMY-2 genes, as well as gyrA mutations; whereas ColpVC, IncHI2A, IncHI2, IncFIA, Inc11, IncA/C2, IncR, IncX1 and po111 plasmids were detected. In addition, phylogenetic analysis revealed multiple independent lineages such as S. enterica serovars S. Infantis, S. Schwarzengrund, S. Minnesota, S. Kentucky and S. Brandenburg. In brief, occurrence and persistence of international lineages of S. enterica serovars in the food production chain is supported by conserved genomes and wide virulome and resistome. In Monte III, we subsequently reported an important observation from the epidemiological point of view of the early emergence of qnrE1 gene in S. Typhimurium. We provide in this study, new insights into the qnrE1 genetic environment and suggest that the emergence of qnrE1 is much earlier than previously thought. It is likely that unless a continuous surveillance is established, we will continue to underestimate the prevalence of these and other antimicrobial resistance (AMR) genes at the environmental-animal-human interface. In Monte IV, we addressed an investigation using WGS analysis and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) genotyping that was able to reveal rare antibiotic-resistant S. enterica serovars isolated from the food production chain. Technologically, our results illustrate how this WGS-CRISPR combined approach constitutes a useful means to decipher the phylogenetic relationships between and provide high-resolution genotyping of Salmonella strains. These results also confirm the potential of CRISPR-based approaches to typifying various Salmonella strains, including infrequent serotypes. Finally, in Monte V, we aimed to study the rising S. Heidelberg serotype, an emerging multi-drug resistant (MDR) serotype in Brazilian food chain. A total of 81 (100%) S. Heidelberg strains were pheno- and genotypically resistant, whereas 91.3% were multidrug resistant. Presence of antimicrobial resistance genes and plasmids demonstrated little variation across the strains. The broad distribution and abundance of S. Heidelberg in the farms, slaughterhouse, transport, lairage and retail market suggests high adaptability of this serovar in the poultry production chain in Brazil. In summary, our findings underscore the potential role of S. Heidelberg as key pathogen in the Brazilian poultry production chain. Overall, our results demonstrate the emergence of new resistance mechanisms and a high distribution of MDR S. enterica serovars isolated in different years from distinct hosts and regions in Brazil, which likely contribute to the dissemination of resistant foodborne pathogens to humans in the food chain. These results highlight the importance of food-producing animals serving as an important reservoir of genes, which confer resistance to the most important antibiotics for human and veterinary medicine. Multiple resistance, and in particular resistance to drugs of last resort are cause for public health concern. In Brazil, we have reported a broad host range of pathogens of great importance to Brazilian agribusiness particularly, since Brazil is the second largest chicken meat producing country globally and the largest exporter of this product with a high domestic consumption. Further, these results suggest the wide dissemination of MDR isolates/serotypes showing high genomic identity regionally which suggests that plasmid promiscuity contributes to the endemic spread. Therefore, continued surveillance of S. enterica in the food chain needs to be established as a national priority with characterization at the genome level if Brazil wishes to prevent the further spread and emergence of new serotypes or resistance attributes.